Long-term survival after ALK-TKI resistance through immunotherapy combined with chemotherapy in ALK-positive non-small cell lung cancer: a case report - Fu, Caihong; Yang, Lei; Qiao, Hui; Liu, Xiting; Wang, Jiexin (Frontiers in Oncology, 2025)
Anaplastic lymphoma kinase (ALK) gene fusions represent one of the most common driver mutations in non-small cell lung cancer (NSCLC). Currently, targeted drug options for ALK fusion-positive patients exhibit diversity, with third-generation drugs achieving a 5-year progression-free survival (PFS) rate exceeding 60%. Nevertheless, for advanced patients, targeted therapy serves as palliative treatment, with the inevitability of disease progression and the development of therapeutic resistance over time. Yet, there are no unified standards regarding progression patterns, resistance mechanisms, or subsequent treatment strategies. The use of immune checkpoint inhibitors (ICIs) in ALK fusion-positive patients remains highly controversial, and clinical data on whether immune checkpoint inhibitor-based therapy can be administered sequentially after progression on ALK Tyrosine Kinase Inhibitors (ALK-TKI) treatment are limited. This case presents a patient with ALK fusion-positive disease who progressed rapidly after receiving first-generation ALK-TKI followed by second-generation ALK-TKI therapy, along with radiotherapy targeting primary and metastatic lesions. Following chemotherapy combined with immunotherapy, the patient achieved a median response duration of more than 45 months.